Powder fabrication and laser additive manufacturing of MoSiBTiC alloy. (January 2019) - Zhou, Weiwei; Sun, Xiaohao; Tsunoda, Kengo; Kikuchi, Keiko; Nomura, Naoyuki; Yoshimi, Kyosuke; Kawasaki, Akira
Abstract: The MoSiBTiC alloy is one promising candidate for ultrahigh–temperature materials. However, it faces severe challenges in the machining of complex shapes because of its significant brittleness, high melting point, and stiffness. To overcome this challenge, we have successfully fabricated MoSiBTiC alloy parts via laser powder bed fusion (L-PBF). A combination of arc-melting and controllable high-energy ball milling (HEBM) was employed to prepare suitable MoSiBTiC powders for L-PBF. The evolution of powder morphology, constituent phases, and laser absorptivity, as well as particle size and distribution during HEBM, was investigated. Moreover, the effects of L-PBF parameters on the densification, microstructure, and mechanical performance of MoSiBTiC alloy builds were studied. A dense MoSiBTiC alloy, mainly consisting of a Mo solid-solution, Mo5 SiB2, Mo2 C, and TiC phases, was obtained at an energy density of 156 J mm −3 using the laser power of 70 W. Compared to the as-cast alloy, the L-PBF-processed MoSiBTiC alloy possessed more uniform and finer grain structures, while exhibiting a lower Vickers hardness due to the existence of internal microcracks. It was also proved that the small quantity of ZrO2 particles from HEBM processing was uniformly imbedded in L-PBF builds. This work may offer significant guidance for designing and producing complexly shaped refractory intermetallics with unique microstructures in ultrahigh–temperature applications. Graphical abstract: Highlights: Additive manufacturing of MoSiBTiC alloy for ultrahigh–temperature material was firstly attempted. An effective approach was developed and optimized for large-scale production of starting MoSiBTiC powders. High-density MoSiBTiC alloy (∼99.8%) was produced via optimizing laser processing conditions. Additive-manufactured MoSiBTiC alloy had more uniform and finer grain structures than as-cast one.